2017
DOI: 10.1093/deafed/enx029
|View full text |Cite
|
Sign up to set email alerts
|

Achievement, Language, and Technology Use Among College-Bound Deaf Learners

Abstract: Deaf learners are a highly heterogeneous group who demonstrate varied levels of academic achievement and attainment. Most prior research involving this population has focused on factors facilitating academic success in young deaf children, with less attention paid to older learners. Recent studies, however, have suggested that while factors such as early cochlear implantation and early sign language fluency are positively associated with academic achievement in younger deaf children, they no longer predict ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…National (U.S.) data drawn from the National Longitudinal Transition Study 2 (NLTS2) further indicate that using spoken language, but neither using sign language nor having deaf parents, is a significant predictor of mathematics achievement among deaf secondary school students (Marschark, Shaver, et al, 2015). Similar findings have been obtained in several other large-sample studies by Convertino, Marschark, Sapere, Sarchet, and Zupan (2009), Crowe, Marschark, Dammeyer, and Lehane (2017), Dammeyer and Marschark (2016), and Geers, Tobey, Moog, and Brenner (2008).…”
Section: Mathematics Performance Sign Language and Visual-spatial Ssupporting
confidence: 91%
See 2 more Smart Citations
“…National (U.S.) data drawn from the National Longitudinal Transition Study 2 (NLTS2) further indicate that using spoken language, but neither using sign language nor having deaf parents, is a significant predictor of mathematics achievement among deaf secondary school students (Marschark, Shaver, et al, 2015). Similar findings have been obtained in several other large-sample studies by Convertino, Marschark, Sapere, Sarchet, and Zupan (2009), Crowe, Marschark, Dammeyer, and Lehane (2017), Dammeyer and Marschark (2016), and Geers, Tobey, Moog, and Brenner (2008).…”
Section: Mathematics Performance Sign Language and Visual-spatial Ssupporting
confidence: 91%
“…In an analysis of the NLTS2 data from secondary school students in the United States, Marschark, Shaver, et al (2015) found that use of spoken language but not CI use was a significant predictor of mathematics, reading comprehension, social studies, and science among deaf secondary school students. Convertino et al (2009) and Crowe et al (2017) also failed to find CI use to be a predictor of mathematics ability among college-bound, deaf secondary school students as indicated by college entrance examination scores. Crowe et al found students’ self-rated spoken language skills the best predictor of reading and English test scores and a positive predictor of mathematics and science scores.…”
Section: Mathematics Performance Spoken Language and Cochlear Implamentioning
confidence: 88%
See 1 more Smart Citation
“…The lack of overall significant differences in social maturity between deaf and hearing university students, between those who primarily used sign language or spoken language, or between CI users and deaf nonusers replicated findings of Marschark et al (2017). The last of these findings also is consistent with the lack of academically-related differences between CI users and deaf nonusers at the university level (e.g., Convertino et al, 2014; Crowe et al, 2017). It remains possible, however, that there may be different foundations of social maturity between deaf CI users and deaf nonusers and between deaf and hearing individuals more broadly.…”
Section: Resultssupporting
confidence: 61%
“…A second issue in need of further examination derives from several studies that have reported social-emotional advantages to deaf children after cochlear implantation, at least among those with better spoken language skills (e.g., Bat-Chava & Deignan, 2001; Jambor & Elliot, 2005; Wheeler, Archbold, Gregory & Skipp, 2007). Marschark et al (2017), however, did not find social maturity differences between CI users and deaf nonusers, and other studies have found that by secondary school age, early advantages among CI users relative to deaf nonusers in vocabulary, reading, and other academic domains are attenuated or absent (Convertino, Borgna, Marschark, & Durkin, 2014; Crowe, Marschark, Dammeyer, & Lehane, 2017; Geers, Tobey, Moog, & Brenner, 2008; Marschark, Shaver, Nagle, & Newman, 2015). Long-term influences of cochlear implantation on social behaviour have not been explored, and it may be that early advantages in that domain are later attenuated, just as they are in language and academic domains.…”
Section: Introductionmentioning
confidence: 68%